STUDY OF METHODS AND CORRECTIONAL WORK OF MEDICAL UNIVERSITY TEACHERS - Kasymova Nargiza Dilmuratovna (Galaxy International Interdisciplinary Research Journal, 2022)
The article discusses Western countries' methods in the field of medicine, as well as competent supportive analyzes of medical educators and practical recommendations.